Decrease in walking ability with increased functional connectivity between multiple brain areas in Parkinson’s disease: a functional near-infrared spectroscopy study - Wang, Jin; Lu, Jiewei; Wang, Yue; Shu, Zhilin; Cheng, Yuanyuan; Zhang, Xinyuan; Yu, Yang; Han, Jianda; Zhu, Zhizhong; Yu, Ningbo; Wu, Jialing (Frontiers in Aging Neuroscience, 2024)
Introduction: Gait disturbances significantly impact the mobility and quality of life of individuals with Parkinson's disease (PD). This study aims to delve into the cortical mechanisms underlying gait disorders in Parkinson's disease, specifically focusing on the prefrontal cortex (PFC), premotor cortex (PMC), and primary somatosensory cortex (PSC).Objective： To compare the functional connectivity of PFC, PMC, and PSC regions during walking between individuals with Parkinson's disease and healthy controls.The study included 30 individuals with PD (mean age 62.40 ± 7.16 years) and 22 healthy older adults (mean age 60.95 ± 6.34 years). All participants were requested to walk back and forth at a comfortable pace for 30 seconds over a 10-meter course three times. A mobile functional near-infrared spectroscopy (fNIRS) system was employed to evaluate the oxyhemoglobin concentration change (∆HbO2). To assess the interactions between the PFC, PMC, and PSC, the connectivity strength between different fNIRS channels was computed. Results: Individuals with PD in the off-state exhibit significantly decreased walking speed and shorter stride length compared to the health controls. For six brain regions including the left (L) and right (R) PFC, PMC, and PSC, no significant differences in functional connectivity within each region were found between the PD and control groups. However, when it comes to the functional connectivity between every two regions, the PD group exhibited stronger functional connectivity than the control group in LPFC-LPMC, LPFC-RPMC, LPFC-LPSC, RPFC-LPMC, RPFC-LPSC, LPMC-LPSC, LPMC-RPSC, and RPMC-RPSC. Positive correlations were found between gait performance (speed and stride length) and functional connectivity within the RPMC as well as between the RPMC and the RPSC.Individuals with PD exhibit notable gait disturbances during the off-state and increased functional connectivity in brain regions responsible for sensorimotor integration and motor function.Strengthening the FC within RPMC and between RPMC and RPSC could be a potential target for future treatments of gait impairment PD.